RESPONSE OF SOFT WINTER WHEAT VARIETIES ON SOILCLIMATIC CONDITIONS OF DIFFERENT ZONES OF UKRAINE - A. L. Ulich (Зерновое хозяйство России)
The article gives the experimental results of response of the new soft winter wheat varieties on cultivation under different soil-climatic conditions of Ukraine. It has been established that productivity and its stability significantly depends on the placing of the varieties in the proper agro ecologic conditions of soil-climatic zones, subzones and microzones, including the favourable and unfavourable years. The new varieties reveal specific response to agro ecologic conditions of macroand microzones. To realize their productive potential it is expedient to apply a differentiated approach to the placing of the varieties in the agro ecologic zones, subzones and microzones according to the requirements of the biologic traits of the varieties, their adaptive ability and the conditions of ecologic environment of the zones. The mutually complementary varieties with high adaptability, better response to the favourable agro ecologic conditions, more tolerant and resistant to the unfavourable conditions have been revealed and recommended for the use in the soil-climatic zones, subzones and microzones. According to the parameters of productivity and ecologic adaptability, the varieties ‘Sotnitsa’, ‘Kalanch’, ‘Gurt’, ‘Tonatsiya’, ‘Dobrochin’, ‘Gubernator Dona’ should be grown in the Steppe zone; the varieties ‘Sotnitsa’, ‘Oriyka’, ‘Lira Odesskaya’, ‘Tatsius’, ‘Fidelius’ should be grown in the forestry steppe zone; the varieties ‘Tatsius’, ‘Fidelius’, ‘Seylor’, ‘Etela’ should be grown in the marshy woodlands zones. The other varieties showed better characteristics in the other subzones and microzones. To determine and select the mutually complementary varieties, which can more efficiently realize their agro ecologic and genetic potentials with the different resource and technical supply, it’s necessary to study the peculiarities of the variety response on the agro ecologic conditions in the soil-climatic macroand microzones using the scientifically substantiated methods.